A Qualitative Exploration of Predictive Maintenance Practices in Bali - Wiratama, Bayu (Journal of Sustainability Industrial Engineering and Management System, 2024)
This study investigates the practices, challenges, and strategic implications of predictive maintenance (PdM) in the industrial sector of Bali, Indonesia, with a particular emphasis on how local organizations conceptualize, implement, and experience PdM within their socio-technical contexts. The research aims to bridge the knowledge gap between global technological paradigms and localized maintenance strategies by exploring the extent to which PdM has been integrated into organizational routines and infrastructure. Employing a qualitative research design grounded in the interpretive paradigm, the study adopts an exploratory case study approach. Data were collected through in-depth semi-structured interviews, document analysis, and site observations across multiple firms in the manufacturing, utility, and infrastructure sectors. Thematic analysis was conducted using NVivo 14, ensuring methodological rigor and triangulation of findings. The study reveals significant variations in organizational awareness, technological readiness, and human capital development related to PdM adoption. Key findings highlight the misalignment between technological investments and actual utilization, as well as the pivotal role of leadership and organizational culture in shaping implementation outcomes. Moreover, the research identifies infrastructural limitations, digital literacy gaps, and vendor dependencies as major constraints, especially for small and medium-sized enterprises. Notably, several firms demonstrated emerging alignment between PdM practices and sustainability goals, suggesting untapped potential for predictive strategies to contribute to broader environmental and operational performance. The study concludes that successful PdM implementation in Bali requires a synergistic combination of technical infrastructure, cultural transformation, and strategic alignment, supported by cross-sectoral collaboration and policy intervention. These insights contribute to the evolving discourse on smart maintenance in emerging economies and offer practical recommendations for industrial managers, policymakers, and technology providers.